PENGARUH IMPLEMENTASI METODE E-BILLING DAN MANUAL UNTUK WAJIB PAJAK BADAN TERHADAP PENERIMAAN PAJAK - Mardianto, Totok (JEB17 : Jurnal Ekonomi dan Bisnis, 2026)
This research aims to obtain empirical evidence whether there is an influence of the application of e-billing methods and corporate taxpayer manuals on tax revenues at the Surabaya Pratama Tax Service Office. The population in this study were all corporate taxpayers registered at the Surabaya Pratama Tax Service Office. The sample used a purpose sampling method based on judgment (Judgment Sampling). The data used is secondary data in the form of total tax revenue, both nominally and by number of transactions. The statistical method used to test the hypothesis is multiple regression analysis and difference tests. Based on the results of the analysis carried out, it shows that in nominal data the application of e-billing does not have a significant effect on tax revenues, while manual receipts have a significant effect. In transaction data, the application of e-billing and manual methods has a significant effect on tax revenues. The variable method of implementing e-billing and manual has more influence on tax revenue on transaction data than nominal data at KPP Pratama Surabaya. Keywords: e-billing method, manual method, and tax revenue